Fibroblast growth factor receptor 2 (FGFR2) genetic polymorphisms contribute to fused roots in human molars - Sandra Regina Santos Meyfarth; Flares Baratto-Filho; Maria Eduarda Nunis Locks; Peter Proff; Giordano Oliveira Zandoná; Thaís de Oliveira Fernandes; Paulo Henrique Condeixa de França; Christian Kirschneck; Leonardo Santos Antunes; Erika Calvano Küchler (PLoS ONE, 2025)
Fibroblast growth factors (FGFRs) signaling are required for human tooth development. Its dysregulation affects tooth formation and patients with FGFR2 mutations often present dental anomalies in the spectrum of the syndrome. This study aimed to investigate whether genetic polymorphisms in FGFR2 are associated with molar fused roots. The null hypothesis is that genetic variations in FGFR2 are not associated with isolated cases (non-syndromic) of molars fused roots. Panoramic radiographs of non-syndromic patients were used to assess the occurrence of fused roots in molars. Genomic DNA analysis was performed to investigate polymorphisms within the candidate gene. The association between fused roots and genetic polymorphisms was analyzed using allelic and genotypic distributions, and haplotype frequencies. Odds ratio and 95% confidence interval were calculated to assess the chance of presenting fused roots. The significance level was set at p <  0.05 for all the analysis. A total of 170 patients were included. Statistically significant differences in genotype distribution were observed in rs10736303 and rs2162540. Individuals carrying at least one G allele of rs10736303 had an increased chance to present fused roots. A total of 154 haplotype combinations demonstrated statistically significant associations. The polymorphisms rs10736303 and rs2162540 in FGFR2 were associated with fused roots in human molars.